Long Term Evolution Band Selectable Digital up Converter - Gowda, Nayana (International Journal of Reconfigurable and Embedded Systems (IJRES), 2021)
Wireless base-station Radio consists of many important blocks like Digital Front end (DFE), Digital to analog converters(DAC) , Analog to Digital converter(ADC) and many analog amplifiers to transmit and receive the required RF signals. DFE blocks helps in easy configuration of the carriers within the spectrum available. Performance of a Radio mainly depends on the better implementation of the DFE. The output of the Base band signals are fed to the DFE block which implements the required changes to the input signal and feeds the data to a higher sample rate DAC for downlink, this process of up sampling of data is done by Digital Up convertor (DUC) block which is a part of the DFE. Similarly the DFE takes processed digital converted data from the ADC and down converts the signal to the baseband sample rate for further processing. This Process of down sampling of data is done by Digital down convertor (DDC) block which also is a part of the DFE. The number of antenna ports and the number of carrier required to configure per antenna port defines the requirement of for the Number of DUC & DDC paths to be used in the DFE design. If there are 4 antenna ports and single carrier configuration per antenna port then the number of DUC block required will be 4 for this design. Hence the effective implementation of the DUC/DDC block will define the effective resource requirement for a DFE design.